1999
DOI: 10.1074/jbc.274.53.38097
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulatory Elements of the Human Gene for Cytochrome P450c21 (Steroid 21-Hydroxylase) Lie within Intron 35 of the Linked C4B Gene

Abstract: The CYP21 gene, which encodes P450c21, the adrenal steroid 21-hydroxylase needed for glucocorticoid synthesis, lies in the major histocompatibility locus only 2.3 kilobase pairs (kb) downstream from the C4 gene. A 300-base pair (bp) proximal promoter and two upstream regions within C4 are needed for expression of mouse CYP21; the human gene also has a proximal promoter, but upstream elements have not been studied. To search for upstream regulatory elements in human CYP21B, we examined up to 9 kb of 5-flanking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…Among them, the human CYP21A2 gene has a distal transcriptional regulatory element "Z promoter," which lies in intron 35 of the upstream gene C4B (Wijesuriya et al 1999). From the genomic comparisons, we found a conserved noncoding DNA segment exactly at the correct position at intron 35 in the human C4B gene as well as in the mouse C4B gene (Fig.…”
Section: Conserved Noncoding Sequences (Cns) and Gene Regulationmentioning
confidence: 86%
“…Among them, the human CYP21A2 gene has a distal transcriptional regulatory element "Z promoter," which lies in intron 35 of the upstream gene C4B (Wijesuriya et al 1999). From the genomic comparisons, we found a conserved noncoding DNA segment exactly at the correct position at intron 35 in the human C4B gene as well as in the mouse C4B gene (Fig.…”
Section: Conserved Noncoding Sequences (Cns) and Gene Regulationmentioning
confidence: 86%
“…These cells secrete the same steroids that are produced by the human adrenal (Gazdar et al 1990), and express all the enzymes normally found in the human fetal adrenal gland (Staels et al 1993). The regulation of steroid hormone synthesis, the regulation of the mRNAs for the steroidogenic enzymes and the transcriptional regulation of their cognate genes all respond in the physiologically expected fashions, providing excellent evidence that the regulation of steroidogenesis in these cells is a useful model for the regulation of steroidogenesis in the human fetal adrenal (Gazdar et al 1990, Rainey et al 1993, Staels et al 1993, Rainey et al 1994, Bird et al 1995, Rodriguez et al 1997, Bird et al 1998, Wijesuriya et al 1999, Lin et al 2001. The potential action of Dex on the adrenal could conceivably be exerted at any of three levels.…”
Section: Resultsmentioning
confidence: 99%
“…They produce all of the steroids and express all of the enzymes of human adrenal steroidogenesis, and regulate the genes encoding these enzymes in a manner similar to that of human fetal adrenal cells (Gazdar et al 1990, Staels et al 1993, Rainey et al 1993, 1994, Bird et al 1995, Rodriguez et al 1997, Bird et al 1998, Wijesuriya et al 1999, Lin et al 2001. They also express insulin-like growth factor-II (Staels et al 1993), a marker of the fetal but not the adult adrenal (Voutilainen & Miller 1988), and express functional glucocorticoid receptor (Fassnacht et al 2000, Feltus et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…HepG2, JEG3 (37), and HEK293 (38) cells were grown as described. NCI-H295A cells from several plates were collected by scraping, washed with chilled phosphate-buffered saline (PBS), suspended in 50 mM sodium phosphate containing 150 mM KCl, and lysed by sonication.…”
Section: Methodsmentioning
confidence: 99%